2014
DOI: 10.1139/cjz-2014-0049
|View full text |Cite
|
Sign up to set email alerts
|

Context dependence of elk (Cervus elaphus) vigilance and wolf (Canis lupus) predation risk

Abstract: To assess the relationship between predation risk perceived by elk (Cervus elaphus L., 1758) as evidenced by vigilance, we conducted focal animal observations in elk winter range. We stratified our observations in Glacier National Park, Montana, USA, and Waterton Lakes National Park, Alberta, Canada, in valleys with three wolf (Canis lupus L., 1758) population levels (Saint Mary Valley: no wolf; Waterton Valley: moderate wolf; North Fork Valley: high wolf). Although the lowest elk vigilance occurred in Saint M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 40 publications
(54 reference statements)
0
11
0
Order By: Relevance
“…Similarly, Hamilton et al (1980) concluded that most browsing by moose took place within 80 m from forest cover and browsing intensity dropped significantly beyond 80 m. Both these studies suggest that effects of predation risk on moose only occur in larger clear-cuts, with at least 100 m distance to edge. In contrast, in areas with low to moderate wolf presence, elk did not increase vigilance levels with increasing distance to forest edge (Eisenberg et al 2014) and increased their use of preferred grassland foraging habitats (Creel et al 2005). Since we took a random selection of clear-cuts in our study area, this indicates that clear cuts in our study region are generally smaller (i.e.…”
Section: Differences In Tree Height and Density Not Wolf Predation Rmentioning
confidence: 87%
See 3 more Smart Citations
“…Similarly, Hamilton et al (1980) concluded that most browsing by moose took place within 80 m from forest cover and browsing intensity dropped significantly beyond 80 m. Both these studies suggest that effects of predation risk on moose only occur in larger clear-cuts, with at least 100 m distance to edge. In contrast, in areas with low to moderate wolf presence, elk did not increase vigilance levels with increasing distance to forest edge (Eisenberg et al 2014) and increased their use of preferred grassland foraging habitats (Creel et al 2005). Since we took a random selection of clear-cuts in our study area, this indicates that clear cuts in our study region are generally smaller (i.e.…”
Section: Differences In Tree Height and Density Not Wolf Predation Rmentioning
confidence: 87%
“…As a result elk moved into the protective cover of wooded areas when wolves were often present. In contrast, in areas with low to moderate wolf presence, elk did not increase vigilance levels with increasing distance to forest edge (Eisenberg et al 2014) and increased their use of preferred grassland foraging habitats (Creel et al 2005). Hence, the wolf density and the frequency at which wolves are present in an area can determine the perceived risk of their prey species for potential risk factors, such as a forest edge.…”
Section: Differences In Tree Height and Density Not Wolf Predation Rmentioning
confidence: 92%
See 2 more Smart Citations
“…Larger animals (ungulates and primates) have been shown to select habitat where the sightlines allow good visibility of approaching predators Abu Baker & Brown, 2013;. Lastly, a number of studies studying wolf-elk interactions show that based on habitat variability the strategies applied by the elk to avoid predation (vigilance, habitat selection) can vary greatly (Hebblewhite, Merrill & McDonald, 2005;Eisenberg et al, 2014) Other strategic choices of prey driven by the predator-prey dynamics can include dietary selection and movement patterns. For example (again in the Heteromyid rodents), foragers better equipped for risk management (kangaroo rats) have a more diverse diet than the foragers less well equipped for predator management (pocket mice) who forage what they can (Davidson, Brown & Inouye, 1980).…”
Section: B Non-consumptive Effects Of Predators: An "Ecology Of Fear"mentioning
confidence: 99%